THE INFLUENCE OF IMPLEMENTATION AND QUALITY OF INTEGRATED REPORTING ON EARNINGS QUALITY WITH AGENCY COST AS THE MODERATING VARIABLE - Dana Manggala Atmaja Herlambang; Faisal Faisal (Diponegoro Journal of Accounting, 2022)
The objective of this study is to examine the effect of the implementation of integrated reporting and the quality of integrated reporting on earnings quality and the effectiveness of integrated reporting implementation on earnings quality, depends on agency cost. This study uses the dependent variable Earnings Quality; independent variable Integrated Reporting Implementation and Quality; Agency Cost moderating variable; and Corporate Governance control variable.The population in this study consists of mining companies in Indonesia Stock Exchange for the period 2017-2020. The number of companies studied were 47 companies with a total of 188 data. This study used moderated regression analysis for hypotheses testing. The results of this study show that the implementation and quality of Integrated Reporting has a significant negative effect on earnings quality. Meanwhile, agency costs managed to moderate the relationship between the application of Integrated Reporting to earnings quality.